The Impact of the Covid-19 Pandemic on Constitutionalism and the State of Emergency - Sinani, Blerton (Public Governance, Administration and Finances Law Review, 2023)
The emanation of the Covid-19 global pandemic has managed to influence specific legal, political and socio-economic aspects. Public health, public institutions, as well as concepts such as: the rule of law, restriction of certain human rights and socio-economic wellbeing became characteristics of the global pandemic and as such triggered a state of emergency. The pandemic cannot be a justified pretext for an unlimited suspension of democracy. Indeed, restrictions on civil rights and liberties ought to be interim, proportional and transparent. Although the emergency measures taken by governments against the Covid-19 should be provisional, timebound and in congruence with democracy as any contemporary political regime or state governed by the rule of law. This situation once again revealed to us the importance of a constitutional state of emergency guided by public law in its forms and examples of comparative constitutional law regarding events which in 2020 demanded the emergence and function of public institutions in an effort to protect society. The state of emergency is regulated by the Constitution of the Republic of North Macedonia of 1991 in general which gives the government expansive power, such as bypassing the parliament’s power through issuing acts by force of law. It is worth mentioning that in North Macedonia there is no lex specialis or special legislative act that regulates a state of emergency.